Effect of hyposalinity on coral bleaching and survival in a hard (Pocillopora damicornis) and soft coral (Sarcophyton sp.) - Kongjandtre, Narinratana; Wattana, Titikarn; Veerapitipath, Varanit; Chinchana, Apisara (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 2 (2022): April-June 2022, 2021)
This study investigates the effect of hyposalinity on coral bleaching in a species of hard coral ( Pocillopora damicornis ) and a soft coral ( Sarcophyton sp.). Corals were exposed to ambient seawater (32 psu) and reduced-salinity seawater (15 psu and 25 psu) for 32 days. Both the hard coral and soft coral were highly affected by the salinity level of 15 psu. Fragments of Pocillopora damicornis were 90% bleached within four days and died after five days of exposure to salinity levels of 15 psu. Similarly, Sarcophyton sp. was 50%-95% bleached within four days and died after seven days of exposure. Both corals were less impacted by exposure to salinity levels of 25 psu and 32 psu; P. damicornis and Sarcophyton sp. were partially bleached but survived until the end of the experiment. We report that P. damicornis is more susceptible to hyposalinity than Sarcophyton sp. The results of this study can serve as basic information for managers regarding the release of freshwater into areas of the ocean with coral reefs. The study also suggests that salinity monitoring during rainy seasons or flooding may allow prediction of future coral bleaching caused by these low-salinity events. Keywords: rainfall, bleaching, scleractinian, soft corals, hyposalinity